Helmets for preventing injury in motorcycle riders. - Liu, B; Ivers, R; Norton, R; Boufous, S; Blows, S; Lo, S (2008)
BACKGROUND: Motorcycle crash victims form a high proportion of those killed or injured in road traffic crashes. Injuries to the head, following motorcycle crashes, are a common cause of severe morbidity and mortality. It seems intuitive that helmets should protect against head injuries but it has been argued that motorcycle helmet use decreases rider vision and increases neck injuries. This review will collate the current available evidence on helmets and their impact on mortality, and head, face and neck injuries following motorcycle crashes. OBJECTIVES: To assess the effects of wearing a motorcycle helmet in reducing mortality and head and neck injury following motorcycle crashes. SEARCH STRATEGY: We searched the Cochrane Injuries Group Specialised Register, Cochrane Central Register of Controlled Trials (The Cochrane Library issue 2, 2007), MEDLINE (up to April 2007), EMBASE (up to April week 16, 2007), CINAHL (January 1982 to February 2003), TRANSPORT (up to issue 12, 2006) (TRANSPORT combines the following databases: Transportation Research Information Services (TRIS) International Transport Research Documentation (ITRD) formerly International Road Research Documentation (IRRD), ATRI (Australian Transport Index) (1976 to Feb 2003), Science Citation Index were searched for relevant articles. Websites of traffic and road safety research bodies including government agencies were also searched. Reference lists from topic reviews, identified studies and bibliographies were examined for relevant articles. SELECTION CRITERIA: We considered studies that investigated a population of motorcycle riders who had crashed, examining helmet use as an intervention and with outcomes that included one or more of the following: death, head, neck or facial injury. We included any studies that compared an intervention and control group. Therefore the following study designs were included: randomised controlled trials, non-randomised controlled trials, cohort, case-control and cross-sectional studies. Ecological and case series studies were excluded. DATA COLLECTION AND ANALYSIS: Two authors independently screened reference lists for eligible articles. Two authors independently assessed articles for inclusion criteria. Data were abstracted by two independent authors using a standard abstraction form. MAIN RESULTS: Sixty-one observational studies were selected of varying quality. Despite methodological differences there was a remarkable consistency in results, particularly for death and head injury outcomes. Motorcycle helmets were found to reduce the risk of death and head injury in motorcyclists who crashed. From four higher quality studies helmets were estimated to reduce the risk of death by 42% (OR 0.58, 95% CI 0.50 to 0.68) and from six higher quality studies helmets were estimated to reduce the risk of head injury by 69% (OR 0.31, 95% CI 0.25 to 0.38). Insufficient evidence was found to estimate the effect of motorcycle helmets compared with no helmet on facial or neck injuries. However, studies of poorer quality suggest that helmets have no effect on the risk of neck injuries and are protective for facial injury. There was insufficient evidence to demonstrate whether differences in helmet type confer more or less advantage in injury reduction. AUTHORS' CONCLUSIONS: Motorcycle helmets reduce the risk of death and head injury in motorcycle riders who crash. Further well-conducted research is required to determine the effects of helmets and different helmet types on mortality, head, neck and facial injuries. However, the findings suggest that global efforts to reduce road traffic injuries may be facilitated by increasing helmet use by motorcyclists.